A review of micromachined sensors for automotive applications. (July 2019) - Mohankumar, P.; Ajayan, J.; Yasodharan, R.; Devendran, P.; Sambasivam, R.
Highlights: Overview of Micromachined sensors for automotive applications. Recent developments in gas, mass airflow and viscosity sensors. Highlights the significance of virtual and RADAR sensors. Point out the use of nanoparticles and nanowire for the development of automotive sensors. Abstract: The development of onboard sensors in combination with internet connectivity provides a better driving experience, which fuels the growth of automotive market. The ever growing sales of automotives across the world and emergence of new automobile technologies such as autonomous vehicles are the key factors driving the growth of automotive sensor market. This review article extensively studies the advancements being made in the developments of automotive sensors for various automotive applications. The highlight of the article is that it analyses the micromachined automotive sensors such as pressure sensors, position, speed, angular rate and rotational speed sensors, mass air flow sensors, inertial, torque and viscosity sensors along with the traditional temperature and pressure sensors. This article also points out the use of nanoparticles, nanowire for the development of automotive sensors for the future autonomous automotive applications.